SERUM URIC ACID LEVELS AND THEIR ASSOCIATION WITH MYOCARDIAL INFARCTION OUTCOMES - Dr. Sravani Karumuru (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Clinical and epidemiological studies have proved that serum uric acid (SUA) is significantly correlated with cardiovascular disease. The present study has been undertaken with the following High uric acid level is a negative prognostic factor in patients with myocardial infarction. In myocardial infarction higher the uric acid level increases the risk of mortality rate. There is uncertainty about the role. This prospective study evaluated the relationship between serum uric acid (SUA) levels and clinical outcomes in 100 patients with acute myocardial infarction (MI). SUA levels were measured on admission, and patients were monitored for heart failure, arrhythmias, ejection fraction, and mortality. The mean SUA level was 5.9 mg/dl, with males having higher levels than females. Patients with SUA levels above 7 mg/dl had significantly lower ejection fractions and poorer Killip classifications. Among patients in Killip class IV, 12 out of 15 had SUA levels above 7 mg/dl, and 4 died from arrhythmias and hypotension. Additionally, patients with ventricular tachycardia (VT) had SUA levels exceeding 7 mg/dl and experienced in-hospital mortality. No significant differences in SUA levels were found between diabetic and non-diabetic patients. The study concludes that elevated SUA at admission is a strong, independent predictor of short-term adverse outcomes, including mortality, in MI patients. SUA measurement can be a cost-effective tool for early risk stratification and guiding treatment strategies.f uric acid in acute coronary syndrome and whether it could be used as a prognostic marker in MI patients. The role of serum uric acid in cardiovascular and renal diseases has been intensively investigated. High serum uric acid has been indicated as a risk factor for CAD and as an independent prognostic factor of poorer outcomes in patients with verified CAD. Study was done in one hundred patients of myocardial infarction at Sri Venkateshwaraa Medical College Hospital and Research Centre, Pondicherry.Detailed history and clinical examination done. Uric acid was estimated. The relationship of uric acid with severity of Myocardial infarction, treatment response, ejection fraction, arrhythmia and hypotension were studied. A total of 100 patients were recruited to the study. The mean age and mean uric acid level of the study sample was 56 years and 5.9mg/dl respectively. There were 65(65%) males and 35(35%) females. Males had higher uric acid level than females. (p7mg/dl (n= 17) had low ejection fraction  which was statistically significant p value ,0.03. Among the 15 patients belonging to KILLIP IV, 12 had SUA values more than 7 mg/dL.(, p